2015
DOI: 10.1016/j.imlet.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A suppresses Th1-type immune response in human peripheral blood mononuclear cells in vitro

Abstract: Bisphenol A (BPA) is a widely used plasticizer, which came into focus because of its genotoxic and sensitizing potential. Besides its toxic properties, BPA is also well-known for its antioxidant chemical properties. This in vitro study investigated the interference of BPA with interferon-γ (IFN-γ)-induced tryptophan breakdown and neopterin production in human peripheral blood mononuclear cells (PBMC). The pro-inflammatory cytokine IFN-γ induces the conversion of the essential amino acid tryptophan into kynuren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…However, all neuronal substances included in the present study are involved in pro- or anti-inflammatory reactions. Strong anti-inflammatory activity is characteristic for VIP and PACAP, which inhibit the synthesis of pro-inflammatory factors [ 56 ], while SP is known as a substance showing pro-inflammatory activity affecting the lymphocytes and macrophages and causing an increase in the level of TNF-α [ 57 ]. In turn, the participation of NO in inflammatory processes is not quite clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, all neuronal substances included in the present study are involved in pro- or anti-inflammatory reactions. Strong anti-inflammatory activity is characteristic for VIP and PACAP, which inhibit the synthesis of pro-inflammatory factors [ 56 ], while SP is known as a substance showing pro-inflammatory activity affecting the lymphocytes and macrophages and causing an increase in the level of TNF-α [ 57 ]. In turn, the participation of NO in inflammatory processes is not quite clear.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with those observed in murine immune system cells, where it has been described that the exposure to high doses (20μM) of BPA increases the proliferation of concanavalin A-stimulated splenocytes [ 36 ] and of thymocytes [ 37 ], while analogous results were found also in goldfish [ 38 ]. By contrast Gostner et al [ 55 ] found a decreased cell viability in human PBMCs treated with micromolar doses of BPA, as well as other studies [ 54 ] reporting an immune-suppression activity of high doses of the chemical in lupus-prone murine models, thus confirming a broad, non-monotonic, BPA effects on immune cells.…”
Section: Discussionmentioning
confidence: 86%
“…BPA, as endocrine disruptor with natural estrogen activity, at small doses can cause different effects from those generated at higher doses, with an oscillating non-monotonic dose response. Numerous evidences, however, have shown that BPA can have significant metabolic and immune effects at environmental low doses, which may not be apparent at higher doses used in traditional toxicological studies [ 13 , 54 , 55 ]. For example, at micromolar doses, the toxic effect on immune cells could regulate expression of a distinct set of genes involved in growth and development, different from those regulated at low doses [ 13 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations